WEDM of Mg/CRT/BN composites: Effect of materials and machining parameters. Issue 1 (2nd January 2018) - Gopal, P. M.; Prakash, K. Soorya; Jayaraj, S.
ABSTRACT: The current work presents a detailed exploration on real-time wire electric discharge machining (WEDM) experiments and grey relational analysis (GRA)–based multi-criteria optimization of material and machining characteristics for lowered surface roughness ( R a ) and improvised material removal rate (MRR) of the newly developed magnesium/boron nitride/cathode ray tube (Mg/BN/CRT) hybrid metal matrix composites (MMCs). The composites were fabricated through powder metallurgy (PM) route by reinforcing silica-rich E-waste CRT panel glass powder crushed for different particle sizes (10, 30, and 50 µm) at various weight percentages (5%, 10%, and 15%) and with 2% boron nitride (BN). Taguchi-based orthogonal array procedure was utilized to formulate the experimental plan for WEDM considering reinforcement level and size, pulse on time ( P on ), pulse off time ( P off ), and wire feed ( W f ) as the input process parameters. ANOVA results reveal that P on and wt% of reinforcement has more effect on R a and MRR than any other considered parameters. The developed mathematical model for R a and MRR predicted values similar to that of experimental results. Multi-criteria optimization was done through GRA technique and the so recommended optimum parameter set furnishes higher MRR (22.34 mm 3 /min) and reduced R a (2.87 µm).